Disease control in crops : (Wiley-Blackwell, 2009)
The control of diseases in crops is still largely dominated by the use of fungicides, but with the increasing incidence of fungicide resistance, plus mounting concern for the environment resulting from excessive agrochemical use, the search for alternative, reliable methods of disease control is gaining momentum. The purpose of this important book is to examine the development and exploitation (or potential for exploitation) of a range of non-chemical approaches to disease control, with a focus on the need for a greater understanding of crop ecology as the basis for effective disease control in the field.